2008
DOI: 10.1186/1471-2350-9-83
|View full text |Cite
|
Sign up to set email alerts
|

Five recurrent BRCA1/2 mutations are responsible for cancer predisposition in the majority of Slovenian breast cancer families

Abstract: Background: Both recurrent and population specific mutations have been found in different areas of the world and more specifically in ethnically defined or isolated populations. The population of Slovenia has over several centuries undergone limited mixing with surrounding populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 35 publications
0
39
0
Order By: Relevance
“…The lowest rate of only 10% was present in families with unilateral breast cancer. According to the reported data and also comparing with other studies [25,26,28,29], the presence of ovarian cancer in association with breast cancer serves as a potential predictive factor for BRCA1 mutation positivity and represents the strongest indication. On the other hand, the presence of bilateral ovarian (17%) or breast (13%) cancer is still stronger criterion for selection as the familiar unilateral cancer.…”
Section: Other Hboc Risk Genes -Tp53 Chek2*1100delc Analysismentioning
confidence: 85%
See 1 more Smart Citation
“…The lowest rate of only 10% was present in families with unilateral breast cancer. According to the reported data and also comparing with other studies [25,26,28,29], the presence of ovarian cancer in association with breast cancer serves as a potential predictive factor for BRCA1 mutation positivity and represents the strongest indication. On the other hand, the presence of bilateral ovarian (17%) or breast (13%) cancer is still stronger criterion for selection as the familiar unilateral cancer.…”
Section: Other Hboc Risk Genes -Tp53 Chek2*1100delc Analysismentioning
confidence: 85%
“…Interestingly, a minimum of nonsense mutations was identified in exon 11 [21,25,26,28,29] in comparison to other types of mutations in this exon and no causal missense mutations were present in this exon due to the lack of highly conserved domain in this region. However, it can not be excluded that some of the frequently occurring missense variants with uncertain clinical significance localized mainly in exon 11 (and similarly in exon 16), might have some effect on the protein function and thus play a role in the development of HBOC phenotype.…”
Section: Other Hboc Risk Genes -Tp53 Chek2*1100delc Analysismentioning
confidence: 99%
“…Sokolenko et al found this single mutation to be present in 4% of unilateral breast cancer patients, in 10% of bilateral cancer patients and in 6% of early‐onset cases (diagnosed at or less than age 40) (16). 5382insC is also a founder mutation in Greece (17), Belarus (18), the Czech Republic (19) and Slovenia (20). It is the second most common BRCA1 mutation in the Ashkenazi Jewish population (8, 9).…”
Section: Discussionmentioning
confidence: 99%
“…In Poland, this mutation accounts for 2.1% of early‐onset breast cancer cases (<50 years) (11), a much lower prevalence than that observed in Belarus. 5382insC is also a founder mutation in other Slavic countries, such as the Czech Republic (12) Slovenia (13) and northern Greece (14) and is the second most common BRCA1 mutation in the Ashkenazi Jewish population (9, 10).…”
Section: Discussionmentioning
confidence: 99%